The corrosion behavior and mechanical properties of 5083 Al-Mg alloy manufactured by additive friction stir deposition. (1st April 2023) - Li, Yidi; Yang, Biaobiao; Zhang, Ming; Wang, Hui; Gong, Wei; Lai, Ruilin; Li, Yunping; Teng, Jianwei
Abstract: Corrosion behavior and mechanical property of 5083 Al-Mg alloy manufactured by additive friction stir deposition (AFSD) were investigated compared with 5083-H112 alloy. AFSD is beneficial to reduce the pitting corrosion sensitivity of 5083 alloy due to refinement and re-dissolution of Mn rich secondary phase particles. But the intergranular corrosion (IGC) susceptibility of AFSD alloy is more significant due to the exfoliation of fine equiaxed grains after sensitization. This can be ascribed to that the grain boundaries of AFSD alloy after sensitization are dotted with β-phase which tends to be attacked by acid. Graphical Abstract: ga1 Highlights: 5083 Al alloy was manufactured by AFSD. AFSD reduced the pitting corrosion of alloy. Intergranular corrosion of AFSD alloy after sensitization is more significant. AFSD alloy showed excellent mechanical property due to fine microstructure.